Manejo de pacientes con preeclapmsia en el servicio de gineco-obstetricia del hospital Isidro Ayora enero 2014 - octubre 2014 - Anaya Lindao, Aldo Julbliner (2014)
This cualitative, descriptive and retrospective investigation called “MANAGEMENT OF PATIENTS WITH PREECLAMPSIA IN THE GYNECOLOGY - OBSTETRICS SERVICE OF ISIDRO AYORA HOSPITAL FROM JANUARY 2014 - OCTOBER 2014”, is focused about knowing the integral management of pregnant who who suffered of preeclampsia, in other words, the treatment and termination way. So, the principal objectives are: Determinate the management of the patients with preeclampsia. Identificate the frequency of toxemia in pregnancy in primiparous and multiparous women. To know the profilaxis of the convulsion crisis in the preeclampsia’s patients. To know the way of ending pregnancy of preeclamptic patients. I have the following results: The total sign was 65 pregnant women since January 2014 to the middle of October, in who applicate the Register Sheet, about the obstetric characteristics, the 58, 46% of preeclamptic’s women were pregnant before. About the management of hypertensive crisis the 58,45% was processed with Hidralazine 5mg in bowl, twice. Meanwhile, the convulsion crisis profilaxis were managed with Magnesio’s Sulfatus in the 72, 31% and 27, 69% didn´t have profilactic treatment, because wasn´t be necessary. Also, we have to say that the abdominal way had predominance in the end of pregnancy in the 70,77% of the cases. KEY WORDS: Preeclampsia, Pregnancy, Treatment.